EVALUATION IN DISTANCE LEARNING IN ENGLISH COURSES: A CASE STUDY OF NON-ENGLISH DEPARTMENT STUDENTS - Yulia Rizki Ramadhani; Jainal Abidin (Institut Pendidikan Tapanuli Selatan, 2021)
This research was carried out to evaluate English learning in Non-English Department Students at Graha Nusantara Padangsidimpuan University by using the Kirkpatrick Evaluation Model for optimization in distance or online learning. Kirkpatrick's evaluation model consists of level 1 reaction, level 2 learning, level 3 behavior, and level 4 result. Of the four levels for the Kirkpatrick Model Evaluation, each is assessed using a different assessment tool and data collected using questionnaires and interviews and data analysis techniques with descriptive statistics. The Slovin formula determines the object of this research with a margin of error of 5% who is a non-English student of the University of Graha Nusantara Padangsidimpuan. The result showed that each of the Kirkpatrick Evaluation model's components had been appropriately applied. Students are expected to be more active in studying material from various sources and practicing many questions to improve their understanding through online learning. It recognized the value of studying for the future, forming online study groups with friends to encourage a desire to learn, and engaging in activities that can boost knowledge while lying down, such as watching learning videos or using other learning resources on smartphones.